The Operas of Pascal Bentoiu: Themes, Collective Character, Ars Choralis - Radu-Țaga Consuela (Sciendo, 2019)
Pascal Bentoiu dedicated to the lyrical stage three opuses: the comedy The Love Doctor, the radio opera The Sacrifice of Iphigenia and the tragedy Hamlet. The female choir from The Sacrifice of Iphigenia and the choir from Hamlet use different ways of vocal expression, adapted to vibrations of the word: from recitative chanting or spoken chorus, to melodic articulations. The hegemony of the vocal parameter and the lyrical expression are counterpoised by the feverishness of the dramatic moments. Pascal Bentoiu proposes new elements in the structure of the opera genre, because in Hamlet the conceptual meanings of the overture are replaced by the choral prelude à cappella. The moments of choral treatment à cappella abound in his operas, these moments being full of emotion and expressing a deep sensitivity.